Structure of a new glycyrrhiza polysaccharide and its immunomodulatory activity - Wu, Yu; Zhou, Hui; Wei, Kunhua; Zhang, Tao; Che, Yanyun; Nguyễn, Audrey D.; Pandita, Sakshi; Wan, Xin; Cui, Xuejie; Zhou, Bingxue; Li, Caiyue; Hao, Ping; et al. (Frontiers in Immunology, 2022)
A component of licorice polysaccharide (GPS-1) was extracted from licorice, its primary structure was identified and characterized for the first time, and its immunomodulatory activity was studied. Crude licorice polysaccharide was isolated and purified by DEAE sepharose FF ion-exchange column chromatography and Chromdex 200 PG gel filtration column chromatography to obtain a purified Glycyrrhiza polysaccharide named GPS-1. NMR and methylation analysis revealed that GPS-1 is composed of homogalacturonan (HG)-type pectin with 4)-D-GalpA-(1 as the backbone. This study of GPS-1 also examined its significant role in regulating immune activity in vitro and in vivo. As a result, GPS-1 promoted the secretion of IFN-γ and IL-4 in mice and increased the proportion of CD3+CD4+ and CD3+CD8+ T lymphocytes in their spleens. Dendritic cells (DCs) treated with GPS-1 showed promotion of DC maturation, antigen presentation, and phagocytic capacity. The results suggest that GPS-1 is a potential immunomodulator that stimulates the immune system by regulating multiple signaling pathways. Combined with our characterization of the primary structure of GPS-1, the present investigation provides the basis for future study of the form-function relationship of polysaccharides.